Insulated Wire Fed Floating Monopole Antenna for Coastal Monitoring - Loni, Zia M.; Espinosa, Hugo G.; Thiel, David V. (Společnost pro radioelektronické inženýrství, 2018)
A thin, flexible, insulated wire submerged in seawater forms a coaxial cable which has attenuation at ultra-high frequency (UHF) dependent on the operating frequency, the diameter of the insulating material and the diameter of the inner conductor. An extension of the insulated wire above the surface through a spherical float forms a monopole antenna. Attenuation through the wire depends on the conductivity and temperature of seawater. This paper reports the effect of electromagnetic (EM) wave propagation at 433 MHz through insulated wires with different radii of the insulating material and inner conductor. The attenuation was calculated and measured in the range of 32-47 dB/m. The propagation from the monopole antenna to a fixed shore based receiver was measured to be approximately equal to 1 dB/m. The propagation measurements were compared with a shielded coaxial cable. Results show that the propagation range depends on the ratio of the insulation radius to conductor radius for insulated wire, however, a shielded coaxial cable showed no significant attenuation. The technique has applications in coastal wireless sensor networks where the water depth changes continually due to tide and wave motion.
Keywords: Floating monopole antenna; ocean wave propagation; wireless sensor networks; insulated wire transmission.